An Overview of the Need for the Curriculum Review In 'Mooting and Litigation' Course - Md Nasir, Nor Ashikin; Abdul Razak, Aida; Abdul Rahim, Asmar; Badarulzaman, Muhammad Hafiz; Mat Rus, Mukhriz (2022)
There are some stages involved in developing a curriculum. Starting from formulating a learning course outline and objectives, then implementation the teaming experiences through the relevant pedagogy and finally to evaluate the teaming outcomes by looking at the achievement of learning objectives through a series of learning experiences. This paper aims to examine the need for the curriculum review for 'Mooting and Litigation (GLUP 4223)', a law course offered by the UUM School of law. The paper also discusses the alignment of the assessment involved with the Course Learning Outcome (CLO). The current syllabus of GLUP4223 including the teaming outcome objectives and teaching-learning methods approved by the University are referred.